2017
DOI: 10.1038/nrc.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for combining targeted and conventional cancer therapy with immunotherapy

Abstract: Over the past 25 years, research in cancer therapeutics has largely focused on two distinct lines of enquiry. In one approach, efforts to understand the underlying cell-autonomous, genetic drivers of tumorigenesis have led to the development of clinically important targeted agents that result in profound, but often not durable, tumour responses in genetically defined patient populations. In the second parallel approach, exploration of the mechanisms of protective tumour immunity has provided several therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
585
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 823 publications
(592 citation statements)
references
References 182 publications
4
585
0
3
Order By: Relevance
“…3). These data support a model where careful scheduling/dosing of mTOR inhibitors can directly benefit anti-tumour immune-checkpoint therapy, 52,53 and provide a clear rationale for exploration of vistusertib/immune checkpoint blockade in the clinic. It is of note that vistusertib treatment resulted in a bell-shaped phenotypic response in T-cells, with the maximal potentiating effect observed at around the IC 50 for pathway inhibition.…”
Section: Discussionsupporting
confidence: 55%
“…3). These data support a model where careful scheduling/dosing of mTOR inhibitors can directly benefit anti-tumour immune-checkpoint therapy, 52,53 and provide a clear rationale for exploration of vistusertib/immune checkpoint blockade in the clinic. It is of note that vistusertib treatment resulted in a bell-shaped phenotypic response in T-cells, with the maximal potentiating effect observed at around the IC 50 for pathway inhibition.…”
Section: Discussionsupporting
confidence: 55%
“…The phase 3 trial ONO-4538-12 (ATTRACTION-2) revealed the efficacy and safety of programmed cell death protein 1 (PD-1) blockade by monoclonal antibody nivolumab in Asian patients with esophagogastric (n = 30) and gastric adenocarcinoma (n = 272) [2]. Currently, in terms of a predictor of response to immune checkpoint inhibitor, much focus is being placed on the microsatellite instability (MSI) status [3]. However, little is known about the MSI status in EGJ adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Since the first Food and Drug Administration (FDA)-approved TMA in 1986, the market of TMAs has grown exponentially, with approximately 50 antibodies approved and over 70 expected in 2020. 4 Among them, TMAs targeting the tyrosine kinase receptors that are overexpressed in several tumor cell subsets (eg, trastuzumab [TZ; Trastuzumab-Herceptinhave initiated a new paradigm for targeted therapy.…”
Section: Introductionmentioning
confidence: 99%